2018
DOI: 10.1002/jbm.a.36571
|View full text |Cite
|
Sign up to set email alerts
|

Combinational effects of mechanical forces and substrate surface characteristics on esophageal epithelial differentiation

Abstract: Even the efficacy of substrate and mechanical stimuli in addition to biochemical cues have been recognized in many studies of stem cell differentiation, few studies have been reported on the differentiation into esophageal epithelial cells. Therefore, the aim of this study was set to propose a method of differentiating stem cells into esophageal epithelial cells according to biochemical reagent concentration, substrate properties, and mechanical forces. After the concentration of all‐trans retinoic acid was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The fibres mainly ranged in size from 200 to 500 nm (Figure 2f,i). Although the effects of micro/nanotopography were not fully explored in the present study, our previous study demonstrated the effect of a nanofibrous substrate on oesophageal epithelial differentiation (Wu et al, 2018), whereas another study showed that an aligned microfibrous substrate improved muscle differentiation and function (Ebrahimi et al, 2018). Therefore, we hypothesised that the fabricated double-layered scaffold may have a positive role in oesophageal tissue engineering by inducing differentiation of hMSCs to oesophageal epithelial and muscle lineages simultaneously.…”
Section: Immunofluorescence Stainingmentioning
confidence: 79%
See 2 more Smart Citations
“…The fibres mainly ranged in size from 200 to 500 nm (Figure 2f,i). Although the effects of micro/nanotopography were not fully explored in the present study, our previous study demonstrated the effect of a nanofibrous substrate on oesophageal epithelial differentiation (Wu et al, 2018), whereas another study showed that an aligned microfibrous substrate improved muscle differentiation and function (Ebrahimi et al, 2018). Therefore, we hypothesised that the fabricated double-layered scaffold may have a positive role in oesophageal tissue engineering by inducing differentiation of hMSCs to oesophageal epithelial and muscle lineages simultaneously.…”
Section: Immunofluorescence Stainingmentioning
confidence: 79%
“…The basal medium for hMSCs was Dulbecco's modified Eagle's medium with low glucose (Gibco, Grand Island, NY) supplemented with 10% (v/v) heat-inactivated foetal bovine serum (Gibco) and 1% penicillin/streptomycin (Hyclone, Logan, UT). Chemical agents were added to the basal medium to induce oesophageal cell differentiation, based on previous studies (Kurpinski et al, 2010;Wu et al, 2018). In detail, to induce epithelial differentiation, hMSCs were treated with 5 μM all-trans retinoic acid (Sigma-Aldrich), 20 ng/ml epidermal growth factor (PeproTech, London, UK), 5 ng/ml fibroblast growth factor-7 (Sigma-Aldrich), and 0.1 μM dexamethasone (Sigma-Aldrich) on the inner layer.…”
Section: Chemical Stimuli (Induction Medium)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, differentiated daughter cells of stem cells are also a component of the stem cell ecotone [ 156 ] and daughter cells may also generate some sort of mechanical signal to participate in the composition of the mechanical microenvironment. Additionally, these mechanical cues do not have a single effect on stem cells [ 157 , 158 ]. And the combination of different mechanical factors is more conducive to the differentiation of stem cells in a more favourable direction [ 159 ].…”
Section: Discussionmentioning
confidence: 99%
“…3D printing and electrospinning) for 3D esophageal reconstruction [5][6][7][8]. Among them, it was confirmed that the strong elasticity of polyurethane (PU) electrospun nanofiber provide the most appropriate physical properties to withstand esophageal peristalsis [5,9]. In addition, the differentiation potential into the esophageal epithelium and muscle was suggested in the double-structured fibrous layer having a different arrangement [10].…”
Section: Introductionmentioning
confidence: 92%